Sialic acid mediated mechanical activation of β2 adrenergic receptors by bacterial pili - Zoe Virion (Nature Portfolio, 2019)
Meningococcus utilizes β-arrestin selective activation of endothelial cell β2 adrenergic receptor (β2AR) to cause meningitis in humans. Here authors report that Meningococcus triggers β2AR signaling by exerting forces on β2AR glycans that terminally expose N-acetyl-neuraminic acid (sialic acid, Neu5Ac) residues.